The The Implementation of Project Based Learning in EFL Class: Fostering students’ high order thinking and autonomy - ulfatul ma'rifah (DIDAKTIKA, 2022)
High Order Thinking Skills (HOTS) and Autonomy should be an integral part of the teaching and learning process, particularly at the university level to foster students’ critical thinking, creative thinking, and learning autonomy to form a habit as lifelong learners. This is a habit that should be designed not only for assessment purposes, but also for the implementation during classroom teaching process. The purpose of this study is analysed students’ HOTS and learning autonomy for English department students in EFL class to design lesson plan by the implementation of Project Based Learning. Three cognitive domains used as parameters to identify students’ HOTS: analysing, evaluating, and creating, while learning autonomy was portrayed through five aspects as the indicators: determining the objectives, setting the plan, selecting methods and techniques, reflect on learning, and assessing and evaluating the project. This study used mixed method in which three observations were made during the teaching learning process, and questionnaires were distributed to 33 English department students in EFL class. In addition, students were chosen using snowball method and interviewed. Both quantitative and qualitative approach were used to analyse the data. The discovery revealed that indicators and characteristics of HOTS and learning autonomy were presented in a consistent manner during classroom interaction and accomplishing project outside the classroom. Students frequently demonstrate critical and creative thinking in variety of ways when they were participating in the classroom. While learning autonomy portrayed on every stage of accomplishing the project to design lesson plan. The implementation of project-based learning is extremely effective and contribute significantly to foster students’ HOT and autonomy.